Investigation of Drug-Excipients Compatibility for Colloidal Delivery of Therapeutic Chondroitinase - Krishnamoorthy Kannan (Journal of Global Pharma Technology, 2019)
Objective: Proteins and enzymes are marginally stable macromolecules along with certain additives for converting them into suitable drug formulation. The research in pharmaceuticals claims the suitability of wide and variety range of micelles, reverse micelles, unsaturated fatty acids and their esters with glycols act as a protective fence for such therapeutic macromolecules against denaturants in colloidal form. The present study, address preformulation and compatibility study of different additives with bioenzyme- chondroitinase for futuristic colloidal microemulsion formulation. Methods: Initially the solubility of chondroitinase with excipients was determined to obtain suitable aqueous, oil and surfactants phase. FTIR spectra of individual chondroitinase and along with each additive in binary blend form were compared to retain characteristic bands of native protein. It was followed with non-denaturing SDS-PAGE to ensure native conformation of enzyme on gel in presence of additives. Circular dichroism technique was used to investigate stability of primary and secondary structure of enzyme in these binary mixtures. The control and accelerated studies were performed by spectroscopy. Results: Chondroitinase solubility was observed as: phosphate buffer > propylene glycol > glycerol > Tween 80 > Oleic acid. FTIR spectra retained characteristic bands of chondroitinase in binary blends. SDS-PAGE ensured no signs of protein fragments, aggregation or degradation on gel. CD spectra revealed no major loss of enzyme activity. Control and accelerated studies confirmed concentration and purity of enzyme in binary blends in accepted limit. Conclusion: These results demonstrated that the excipients employed in this study were safe as additives with chondroitinase for colloidal formulation. Keywords: Circular Dichroism, FTIR-ATR, SDS-PAGE, Preformulation, Enzyme-additive compatibility, Therapeutic chondroitinase.